Pemanfaatan Biobriket dari Kulit Kakao dan Cangkang Kemiri sebagai Energi Alternatif - Melky Alfazrin; Jumiati Ilham; Ervan Hasan Harun (Transbahasa, 2025)
Various methods have been taken to optimize the availability of fossil bioenergy reserves in Indonesia but have not been able to meet primary energy needs. The continued use of fossil- based energy such as oil, natural gas and coal will have an impact on increasing greenhouse gas emissions and climate stability. The bioenergy potential of biomass sources encourages researchers to conduct research on biomass waste as an alternative energy source. This research was conducted to determine the calorific value, combustion rate and water content of cocoa shell and candlenut shell waste using a mixture of different composition variations. The method used in this research is an experimental method to determine the heat value using a bomb calorimeter, and to determine the combustion rate using a mini gas stove. In the research results, the calorific value contained in sample 9 with variations of 200 grams of candlenut shells, 10 grams of sago flour has a calorific value of 5213.7 cal/gram. The longest burning rate was found in sample 8 with a mixture of 200 grams of candlenut charcoal and 10 grams of tapioca adhesive. Produces 0.203 grams/minute. The water content values in samples with different composition variations obtained results that were far from the SNI 01-6235-200 standard. This was influenced by the pressing pressure being applied not being strong enough and the pressure time being too fast. Other factors are influenced by air temperature and humidit.